Enhancement of Entrepreneurship Skill for Universitas Muhammadiyah Magelang Students - Setiawan, Agus; Al Manan, Oesman Raliby; Primadewi, Ardhin; Purnomo, Tuessi Ari (Journal of Community Services and Engagement, 2018)
Universitas Muhammadiyah Magelang (UMMgl) has a vision of "Superior in Science, Islamic in Behavior" which is responsible for providing students with the skills to be independent after graduating from college. To prepare it, UMMgl emphasises to all students to be independent and superior entrepreneurs, to get it is not easy. The processes of the curriculum, internships, and entrepreneurial incubators also need to be prepared carefully and structured. Being an entrepreneur is not easy, requiring the right mentor and guidance to succeed in growing the entrepreneurial spirit, which is essentially the independence of the souls of UMMgl students. The method proposed in this proposal through several stages of intensive mentoring, including 1) Classroom training with entrepreneurial speakers and practitioners in the form of lectures, discussions, case studies, discovery of exploration, simulation, and testimonials; 2) apprenticeship in the partner industry to improve managerial, financial, technical, and entrepreneurial skills; 3) comparative study to get an explanation directly in the industrial premises of the owner; 4) guidance pattern, 5) supervision pattern; 6) the pattern of providing financial assistance to tenants. The results of this Program are formed by five selected tenants and are considered capable of being entrepreneurs ready to compete in the community.